Do not waste your electrodes – principles of optimal electrode geometry for spike sorting - Tóth, R; Barth, AM; Domonkos, A; Varga, V; Somogyvári, Z (IOP Publishing, 2021)
Objective: This study examines how the geometrical arrangement of electrodes influences spike sorting efficiency, and attempts to formalise principles for the design of electrode systems enabling optimal spike sorting performance. Approach: The clustering performance of KlustaKwik, a popular toolbox, was evaluated using semi-artificial multi-channel data, generated from a library of real spike waveforms recorded in the CA1 region of mouse Hippocampus in vivo. Main results: Based on spike sorting results under various channel configurations and signal levels, a simple model was established to describe the efficiency of different electrode geometries. Model parameters can be inferred from existing spike recordings, which allowed quantifying both the cooperative effect between channels and the noise dependence of clustering performance. Significance: Based on the model, analytical and numerical results can be derived for the optimal spacing and arrangement of electrodes for one- and two-dimensional probe systems, targeting specific brain areas.